2015
DOI: 10.1007/s11356-015-4347-4
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of nitrate in groundwater and its potential human health: a case study of lower Mae Klong river basin, Thailand

Abstract: Nitrate contamination in groundwater is a worldwide problem especially in agricultural countries. Environmental factors, such as land-use pattern, type of aquifer, and soil-drainage capacity, affect the level of contamination. Exposure to high levels of nitrate in groundwater may contribute to adverse health effects among residents who use groundwater for consumption. This study aimed to determine the relationship between nitrate levels in groundwater with land-use pattern, type of aquifer, and soil-drainage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 45 publications
0
30
1
Order By: Relevance
“…This information is useful and will force local decision makers to treat the water before it is supplied to residents. Wongsanit et al (2015) found the risks caused by groundwater nitrate ranged between 0.04 and 4.58 for children in the lower Mae Klong basin, Thailand and between 0.02 and 2.29 for adults. The risks are lower than the present study.…”
Section: Health Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is useful and will force local decision makers to treat the water before it is supplied to residents. Wongsanit et al (2015) found the risks caused by groundwater nitrate ranged between 0.04 and 4.58 for children in the lower Mae Klong basin, Thailand and between 0.02 and 2.29 for adults. The risks are lower than the present study.…”
Section: Health Risksmentioning
confidence: 99%
“…The range of RSC has been observed between -16.90 and 1.92 with an average of -2.83, suggesting good and acceptable quality for irrigation. In the present study, the analytic data were also plotted on the US salinity diagram (USSL 1954) and the Wilcox diagram (Wilcox 1948), both of which consider alkalinity and salinity of irrigation water simultaneously. The US salinity diagram (Fig.…”
Section: Irrigation Water Qualitymentioning
confidence: 99%
“…Thus, nitrate is considered as an indicator parameter to assess the extent of pollution at the vicinity of a facility. Other parameters that indicate pollution are given in Table 3 and include ammonia, nitrite, pH, TDS, P, SO 4 2− , and alkalinity. In addition, the selection of suitable monitoring frequency is essential in order to characterize the variability of the groundwater quality with time.…”
Section: Selection Of Monitoring Parameters and Sampling Frequencymentioning
confidence: 99%
“…Nitrate (NO 3 − ) contamination of groundwater is a serious environmental issue of global concern because of its direct adverse effect on human health via drinking water [1][2][3][4]. Ingestion of excess nitrate in drinking water causes harmful biological effects such as methemoglobinemia, hypertension, infant mortality, goiter, stomach cancer, thyroid disorder, cytogenetic defects, and birth defects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate contamination of groundwater can result in serious health and environmental problems (Burow, Nolan, Rupert, & Dubrovsky, ; Spalding & Exner, ; Wang & Burke, ; Wongsanit, Teartisup, Kerdsueb, Tharnpoophasiam, & Worakhunpiset, ). Nitrate can pose a health threat to infants and children who consume contaminated groundwater (Gatseva & Argirova, ) and can cause eutrophication and algal blooms when it spreads in surface water bodies (Bao, Watanabe, Wang, Hayashi, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%